Revisiting the cooperation matrix for classifying cases of port cooperation - case study - Stamatović, Kristijan (Economic and business review, 2020)
The maritime industry has witnessed transformational changes due to the structural developments in the competitive landscape among maritime stakeholders. These trends lead to cooperation between ports, particularly those sharing common hinterland. This paper extends the existing frameworks for analysing cases of port cooperation among adjacent ports by exploring the relevance of the presence or absence of a national border, thus proposing an upgraded version of the matrix for classifying cases of port cooperation. We operationalize our theoretical findings with a case study of the North Adriatic (NAPA) ports. We conduct in-depth, semi-structured expert interviews with relevant port stakeholders in order to position the NAPA ports within the matrix, as both a group of ports and individual port-pairs.
Keywords: Adriatic Sea; case study; Jadransko morje; management; management pristanišča; pomorski promet; pristanišča; transport